SEPAK TERJANG KELOMPOK TERORIS MUJAHIDIN INDONESIA BARAT - Kolonel Samto Hadi Isnanto (Jurnal Universitas Paramadina, 2015)
AbstrakThe terrorist group Mujahidin Indonesia could be a momentary phenomenon when the group has a different way to the other terror groups in Indonesia to collect fund. The group is focused through criminal acts that involving leaders of the group, together with members in the field. The action period ofthis group is relatively short compared to other terror groups, especially the absence of a strong successor that make this group easily quelled by the authorities. But the interesting part of this group is that they can be regarded as the first terror groups in the reform era that using criminal acts in carrying out its operations and recruit members. And the difference, theyare still able to recruit members who are generally Indonesian teenage even though the way is a criminal activity that clearly violate the law.